Evaluation of adding the community reinforcement approach to motivational enhancement therapy for adults aged 60 years and older with DSM‐5 alcohol use disorder: a randomized controlled trial. (1st November 2019) - Andersen, Kjeld; Behrendt, Silke; Bilberg, Randi; Bogenschutz, Michael P.; Braun, Barbara; Buehringer, Gerhard; Ekstrøm, Claus Thorn; Mejldal, Anna; Petersen, Anne Helby; Nielsen, Anette Søgaard
Abstract: Aim: To examine whether adding the Community Reinforcement Approach for Seniors (CRA‐S) to Motivational Enhancement Therapy (MET) increases the probability of treatment success in people aged ≥ 60 years with alcohol use disorder (AUD). Design: A single blind multi‐centre multi‐national randomized (1 : 1) controlled trial. Setting: Out‐patient settings (municipal alcohol treatment clinics in Denmark, specialized addiction care facilities in Germany and a primary care clinic in the United States). Participants: Between January 2014 and May 2016, 693 patients aged 60+ years and fulfilling DSM‐5 criteria for AUD participated in comparing MET ( n = 351) and MET + CRA‐S ( n = 342). Intervention and comparator: MET (comparator) included four manualized sessions aimed at increasing motivation to change and establishing a change plan. CRA‐S (intervention) consisted of up to eight further optional, manualized sessions aimed at helping patients to implement their change plan. CRA‐S included a specially designed module on coping with age and age‐related problems. Measurements: The primary outcome was either total alcohol abstinence or an expected blood alcohol concentration of ≤ 0.05% during the 30 days preceding the 26 weeks follow‐up (defined as success) or blood alcohol concentration of > 0.05% during the follow‐up period (defined as failure). This was assessed by self‐report using the Form 90 instrument. The main analysis involved complete cases. Findings: The follow‐up rate at 26 weeks was 76.2% (76.9% in the MET group and 76.0% in the MET + CRA‐S group). The success rate in the MET group was 48.9% [95% confidence interval (CI) = 42.9–54.9%] versus 52.3% (95% CI = 46.2–58.3%) in the MET + CRA‐S group. The odds of success in the two conditions did not differ (odds ratio = 1.22. 95% CI = 0.86–1.75, P = 0.26, Bayes factor = 0.10). Sensitivity analyses involving alternative approaches to missing values did not change the results. Conclusions: In older adults with an alcohol use disorder diagnosis, adding the 'community reinforcement approach for seniors' intervention to brief out‐patient motivational enhancement therapy treatment did not improve drinking outcome.